2016
DOI: 10.1016/j.jpeds.2016.01.072
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Factors and In-Hospital Outcomes following Tracheostomy in Infants

Abstract: Objective To describe the epidemiology, risk factors, and in-hospital outcomes of tracheostomy in infants in the neonatal intensive care unit (NICU). Study design We analyzed an electronic medical record from 348 NICUs from 1997–2012, and evaluated the associations between infant demographics, diagnoses, and pre-tracheostomy cardio-pulmonary support with in-hospital mortality. We also determined the trends in use of infant tracheostomy over time. Results We identified 885/887,910 (0.1%) infants who receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 16 publications
3
54
1
1
Order By: Relevance
“…Overall 30‐day mortality for all patients was 4.24%, which is similar to previously published short‐term outcomes but less than previously published longer term outcomes, which were 8.9% to 29% . This difference is likely secondary to the morbid and chronic nature of the underlying etiology requiring the tracheostomy.…”
Section: Discussionsupporting
confidence: 75%
“…Overall 30‐day mortality for all patients was 4.24%, which is similar to previously published short‐term outcomes but less than previously published longer term outcomes, which were 8.9% to 29% . This difference is likely secondary to the morbid and chronic nature of the underlying etiology requiring the tracheostomy.…”
Section: Discussionsupporting
confidence: 75%
“…A second large database study showed an in‐hospital mortality of 6.6% . A recent study of 885 neonatal ICU babies with tracheostomies demonstrated an in‐hospital mortality of 14%, but did not track outcomes after hospital discharge . In comparison, our in‐hospital mortality involved 8 patients (1.9%).…”
Section: Discussionmentioning
confidence: 54%
“…PICU placed tracheostomies frequently result in decannulation, but tracheostomy placement is not without risk. Mortality is variable based on the indications for tracheostomy, with tracheostomy placement commonly offered to our most critically ill, complex diseased children (4,5). Families want to understand the benefits and risks of this critical decision to guide them in their ultimate choice, and presentation of this information should occur prior to consent.…”
Section: Introductionmentioning
confidence: 99%